The first golden hour of breastfeeding: where do we stand? - Bollipo, Suneetha; Pagali, Deepthi; Korrapolu, Harsha B.; Rahman, Mohammed Abdul (International Journal of Contemporary Pediatrics, 2018)
Background: Breastfeeding is the corner stone of child survival, nutrition and development and maternal health. The World Health Organization recommends that all neonates be breastfed within one hour of birth. Early initiation of breast feeding (EIBF) is a sentinel indicator for successful breastfeeding. The aim of this study is to assess the practice of early initiation of breastfeeding among babies delivered in our tertiary care teaching unit and to list out the reasons for delay in implementation. Methods: This study is done on 409 postnatal mothers who delivered in our hospital. All the mother-baby dyads enrolled were interviewed within 12 hours of delivery. Data was collected through clinical records and interview of mothers. Results: EIBF is seen only in 19.8% of babies. Median time of initiation of breast feed is 110 minutes. Primiparous mothers had a delay in initiation of feed (p<0.01). The mothers who received practical support from health care providers had successful EIBF(p< 0.01). The main reasons for delay in feeding were lack of early, uninterrupted skin to skin contact between baby and mother and the separation of mother - baby dyads immediately after delivery. Conclusions: EIBF rate in our centre is extremely low compared to the national standards of 44.6%. Several gaps in EIBF need to be addressed and a strict institutional protocol need to be followed. Periodic review of EIBF rates needs to be done by every institute to achieve a global target of > 90%.